Introduction to real analysis - Nicolaescu, Liviu I. 1964- (World Scientific, 2020)
"This is a text that develops calculus "from scratch", with complete rigorous arguments. Its aim is to introduce the reader not only to the basic facts about calculus but, as importantly, to mathematical reasoning. It covers in great detail calculus of one variable and multi-variable calculus. Additionally it offers a basic introduction to the topology of Euclidean space. It is intended to more advanced or highly motivated undergraduates"--
Keywords: Reelle Analysis